A Validation Study of Pre-Operative Scoring System for Prediction of Difficult Laparoscopic Cholecystectomy in Aims - Chaudhary, Muhammad Adil; Kayani, Ziyad Afzal; Sabir, Farzana; Akhter, Naheed; Saleem, Maryam; Malik, Khizra Kompal (Indus Journal of Bioscience Research, 2025)
Introduction: Laparoscopic cholecystectomy (LC) was first done in 1985, since that time it has widely replaced open cholecystectomy (OC) as the standard of care for symptomatic gallstone disease. Objective: To validate Randhawa’s scoring system designed to predict the difficulty of laparoscopic cholecystectomy keeping intraoperative finding as the gold standard. Materials and Method: This cross-sectional validation study was conducted at the Department of Surgery at AIMS, Muzaffarabad from 01 July 2024 to 31 December 2024. Non-probability consecutive sampling was used to recruit participants for the study. Each patient was assigned a preoperative predictive score based on Randhawa’s scoring system, which included evaluations derived from their medical history, clinical examination, and sonographic findings. Results: Data were collected from 254 patients, with a mean age of 45.2 ± 12.4 years. The majority of the participants were female (68%, n=173), while males accounted for 32% (n=81). The average BMI was 27.8 ± 3.2 kg/m², and the mean gallbladder wall thickness was 3.8 ± 1.1 mm. Palpable gallbladders were observed in 25% (n=64) of patients, while 30% (n=76) had a history of hospitalization. Pericholecystic collection was noted in 18% (n=46) of the cases. Sensitivity was 87.5%, indicating a high ability to correctly identify difficult cases, while specificity was 82.0%, showing reliable exclusion of easy cases. Conclusion: It is concluded that Randhawa’s scoring system is a reliable and effective tool for predicting difficult laparoscopic cholecystectomy, demonstrating strong sensitivity, specificity, and overall accuracy.